الضبطية الإدارية للوالي في التشريع الجزائري - خولة سحيري (My University, 2020)
Abstract : Public administration has a means that it possesses to reconcile public order and administrative control as it is one of the functions through which the state seeks to provide the necessary protection in society, and to maintain public order with its three elements: public security, public health, public tranquility, public morals and morals, and the beauty of elegance and grace to consider them among The most dangerous administrative jobs, as they may harm the public freedoms of individuals, through the methods granted by law to the administrative control authorities. Where we also find the nature of the legal position of the governor in the administrative system includes the study of a set of legislative and regulatory provisions through the legal nature of his position in the Algerian legislation. The governor pays full attention to the central interests assigned to him because he is accountable for that. He exercises a dual role as a representative of the state and an executive body for the state where he exercises two types of political and administrative functions. Here, the duplicative effects of his position are highlighted through judicial oversight, which is considered one of the most effective methods of control, as the governor has the authority of oversight as a guarantee True to individuals' rights and freedoms, as they are a warning and warning to the administration to respect the law . .................. ﻤﻠﺨص : ﻟﻺدارة اﻟﻌﺎﻤﺔ وﺴﻴﻠﺔ ﺘﻤﻠﻛﻬﺎ ﻟﻠﺘوﻓﻴق ﺒﻴن اﻟﻨظﺎم اﻟﻌﺎم واﻟﻀﺒط اﻹداري ﺒﺎﻋﺘﺒﺎرﻩ وظﻴﻔﺔ ﻤن وظﺎﺌف اﻟﺘﻲ ﺘﺴﻌﻰ اﻟدوﻟﺔ ﻤن ﺨﻼﻟﻬﻤﺎ إﻟﻰ ﺘوﻓﻴر اﻟﺤﻤﺎﻴﺔ اﻟﻀرورﻴﺔ ﻓﻲ اﻟﻤﺠﺘﻤﻊ واﻟﺤﻔﺎظ ﻋﻠﻰ اﻟﻨظﺎم اﻟﻌﺎم ﺒﻌﻨﺎﺼرﻩ اﻟﺜﻼث أﻤن ﻋﺎم صحة عامة ، سكينة عام ، والأداب والأخلاق العامة ، وﺠﻤﺎﻝ اﻟروﻨق والرواء ﻻﻋﺘﺒﺎرﻫم ﻤن أﺨطر اﻟوظﺎﺌف اﻹدارﻴﺔ ﻷﻨﻬﺎ ﻗد ﺘﻤس ﺒﺎﻟﺤرﻴﺎت اﻟﻌﺎﻤﺔ ﻟﻸﻓراد وذﻟك ﻤن ﺨﻼﻝ أﺴﺎﻟﻴب ﻤﻨﺤﻬﺎ اﻟﻘﺎﻨون ﻟﺴﻠطﺎت اﻟﻀﺒط اﻹداري . ﺤﻴث ﻨﺠد أﻴﻀﺎ طﺒﻴﻌﺔ اﻟﻤرﻛز اﻟﻘﺎﻨوﻨﻲ ﻟﻠواﻟﻲ ﻓﻲ اﻟﻨظﺎم اﻹداري ﻴﺘﻀﻤن دراﺴﺔ ﻤﺠﻤوﻋﺔ ﻤن اﻷﺤﻛﺎم اﻟﺘﺸرﻴﻌﻴﺔ و اﻟﺘﻨظﻴﻤﻴﺔ ﻤن ﺨﻼﻝ اﻟطﺒﻴﻌﺔ اﻟﻘﺎﻨوﻨﻴﺔ ﻟﻤﻨﺼﺒﻪ ﻓﻲ اﻟﺘﺸرﻴﻊ اﻟﺠزاﺌري. ﻓﺎﻟواﻟﻲ ﻴوﻟﻰ اﻟﻌﻨﺎﻴﺔ اﻟﺘﺎﻤﺔ ﻟﻠﻤﺼﺎﻟﺢ اﻟﻤرﻛزﻴﺔ اﻟﻤﻛﻠف ﺒﻪ ﻷﻨﻪ ﻤﺤﺎﺴب ﺒذﻟك ﻓﻬو ﻴﻤﺎرس دور ﻤزدوج ٬ ﺒﺼﻔﺘﻪ ﻤﻤﺜﻝ ﻟﻠدوﻟﺔ وﻫﻴﺌﺔ ﺘﻨﻔﻴذﻴﺔ ﻟﻠوﻻﻴﺔ ﺤﻴث ﻴﻤﺎرس ﻨوﻋﻴن ﻤن اﻟوظﺎﺌف اﻟﺴﻴﺎﺴﻴﺔ ٕوادارﻴﺔ ﻫﻨﺎ ﺘﺒرز اﻷﺜﺎر اﻻزدواﺠﻴﺔ ﻟﻤرﻛزﻩ ﻤن ﺨﻼﻝ اﻟرﻗﺎﺒﺔ اﻟﻘﻀﺎﺌﻴﺔ اﻟﺘﻲ ﺘﻌﺘﺒر ﻤن أﻨﺠﻊ اﻟطرق ﻟﻠرﻗﺎﺒﺔ ﺤﻴث ﻴﻤﻠك اﻟواﻟﻲ ﺴﻠطﺔ اﻟرﻗﺎﺒﺔ ﻛﻀﻤﺎﻨﺔ ﺤﻘﻴﻘﻴﺔ ﻟﺤﻘوق اﻷفراد وﺤرﻴﺎﺘﻬم ﻷﻨﻬﺎ ﺘﻌﺘﺒر ﺘﻨﺒﻴﻬﺎ وﺘﺤذﻴرا ﻟﻺدارة ﻤن أﺠﻝ اﺤﺘرام اﻟﻘﺎﻨون. ................ Résumé : L’administration publique est un moyen de concilier l’ordre public et le contrôle administratif comme l’une des fonctions par lesquelles l’État cherche à assurer la protection nécessaire dans la société et à maintenir l’ordre public dans ses trois composantes. la morale et l’éthique publiques, et la beauté du rythme et de l’arrogance comme l’une des fonctions administratives les plus dangereuses car elle peut affecter les libertés publiques des individus par des méthodes accordées par la loi aux pouvoirs de contrôle administratif. La nature du statut juridique du tuteur dans le système administratif comprend également l’examen d’une série de dispositions législatives et réglementaires à travers la nature juridique de sa position dans la législation algérienne. Ainsi, en tant que représentant de l’État et organe exécutif de l’État, il exerce deux types de fonctions politiques administratives, mettant en évidence les effets de duplication de son statut par le contrôle judiciaire, qui est l’une des méthodes de contrôle les plus efficaces. Le tuteur a le pouvoir de contrôle comme une véritable garantie de droits. Les individus et leurs libertés car ils sont un avertissement et un avertissement à l’Administration pour le respect de la loi.